2006
DOI: 10.1159/000098315
|View full text |Cite
|
Sign up to set email alerts
|

Teach the Teachers: An Observational Study on Mentor Traineeship in Gynecological Laparoscopic Surgery

Abstract: Background: To evaluate the effect of a mentor traineeship in laparoscopic surgery in a teaching hospital. Method: This observational study was performed between January 1997 and December 2004 at Bronovo Hospital, The Hague, The Netherlands. Since January 2001, an advanced endoscopic gynecologist has mentored a trainee in laparoscopic surgery. Data on the trainee’s procedures preceding (1997–2000) and during the mentor traineeship (2001–2004) were compared. The number and type of procedures performed, complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
2
14
0
2
Order By: Relevance
“…It is known that education by a mentor traineeship is accompanied by a low complication rate and a stable conversion rate [17]. The current study, in which all patients were operated in a mentor traineeship setting, showed a low complication and conversion rate comparable to the results of Kolkman et al [17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is known that education by a mentor traineeship is accompanied by a low complication rate and a stable conversion rate [17]. The current study, in which all patients were operated in a mentor traineeship setting, showed a low complication and conversion rate comparable to the results of Kolkman et al [17].…”
Section: Discussionsupporting
confidence: 82%
“…The intraoperative complication rate (1.3%) in the current study is lower than reported in the study by Meeuwissen et al [12] and comparable to the complication rate published by Kauff et al [13]. In the Netherlands several studies have evaluated the gynaecological laparoscopic skills under residents [17,18]. It is known that education by a mentor traineeship is accompanied by a low complication rate and a stable conversion rate [17].…”
Section: Discussionsupporting
confidence: 77%
“…Guided learning curves have been described previously, and it has been suggested that they result in fewer complications during the learning curve [15,20]. However, when implementing a new technique in this manner in an Table 4 Conversions to laparotomy during study established practice, a few previous conditions should be met.…”
Section: Discussionmentioning
confidence: 99%
“…1). The OSATS included 7 items (respect for tissue, time and motion, instrument handling, knowledge of instruments, use of assistance, flow of operation, and knowledge of the specific procedure) scored on a scale of 0 to a maximum of 5 points per item [15]. If a participating gynecologist reached a minimum score of 4 on each item (7 !…”
Section: Osats and Visiting Surgeonmentioning
confidence: 99%
See 1 more Smart Citation